1996
DOI: 10.1007/bf03011770
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine concentrations during cardiopulmonary bypass

Abstract: Purpose: To describe the serum concentrations of ketamine following a clinically relevant dosing schedule during cardiopulmonary bypass ( C P B ). Methods:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Metabolic species differences could also underlie this apparent dissociation. For example, the half-life of ketamine is just 13 min in a variety of mouse lines (Maxwell et al 2006) compared to 1.4-3 h in humans (McLean et al 1996). Methods like those employed by Majewski-Tiedeken et al (2008) to sustain the acute effects of ketamine may be required to reliably mimic effective human treatments in mice.…”
Section: Discussionmentioning
confidence: 98%
“…Metabolic species differences could also underlie this apparent dissociation. For example, the half-life of ketamine is just 13 min in a variety of mouse lines (Maxwell et al 2006) compared to 1.4-3 h in humans (McLean et al 1996). Methods like those employed by Majewski-Tiedeken et al (2008) to sustain the acute effects of ketamine may be required to reliably mimic effective human treatments in mice.…”
Section: Discussionmentioning
confidence: 98%
“…Although it was reported that peak blood levels of ketamine could be as high as 103 μM, 23 the levels required to maintain anesthesia are usually in the range of 10–20 μM. 24 Experimental evidence provided from in vitro cell culture and in vivo animal studies demonstrated that ketamine could induce neurotoxicity when administered at high doses and/or for prolonged periods. 2529 Thus, in this study, we treated neurons with ketamine (100 μM) to study the effect of ketamine on the NSC proliferation and neuronal apoptosis for 3, 6, and 24 h. The underlying mechanisms of this side effect were investigated by exposing neurons to ketamine for 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that peak blood levels of ketamine were as high as 108 μM [18]. Ketamine levels required to maintain anesthesia were approximately 10–20 μM [19]. In addition, experimental evidence from in vitro cell culture and in vivo animal studies demonstrated that ketamine could induce neurotoxicity when administered at high doses and/or for prolonged periods [2024].…”
Section: Methodsmentioning
confidence: 99%